TAHAP PERLAKSANAAN AMALAN PENGAJARAN SAINS DALAM BAHASA INGGERIS DI SEKOLAH RENDAH DI DAERAH JOHOR - Kassim, Noridah (2009)
Teaching of Science and Mathematics in English have been implemented since 2003 until present. Therefore this research is conducted to survey the implementation of teaching Science and Mathematics in English at primary schools. This research involves 270 students as respondents from primary schools at Johor Bahru district. Questionaire which consists 31 items is used is a = . 81. Data is analyzed using descriptive statistics and inferency . The outcome of this research shows that the level of implementation of teaching Science and Mathematics in English is high with mean value is 2.54. This shows that the it is implemented in schools . The comparison level of implementation of teaching Science and Mathematics between town schools and rural schools shows there is no significance difference. This research also shows there is significance difference between implementation of teaching Science and Mathematics in English with students perception towards teachers. There is also a significant relationship between the implementation of teaching Science and Mathematics in English with students attitude towards Science subject. However there is no significance difference between implementation of Science in English with students achievement in Science subject.